Manajemen Sumber Daya Manusia (MSDM) Pada Lembaga Pendidikan - Khoirunnisaa' Khoirunnisaa' (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2018)
Conceptually human resource management in Indonesia is focused onÂ understanding plan, implementing plan, and greater attention to managerial aspects and better utilization of people as organizational resources. In other words, human resource management is a reflection of the increasing significance regarding the management of people in the organization as well as a broader perspective on the assessment of this field. The urgency of human resource management, among others: First, human resource management is not only ordinary strategic activities, but also is something central in achieving organizational goals. Second, human resource managers hand over responsibility for human asset management to senior line management. Third, there is a shift from